2013
DOI: 10.3109/0886022x.2012.757826
|View full text |Cite
|
Sign up to set email alerts
|

Association of Matrix Metalloproteinase-9 Level with the Risk of Renal Involvement for Henoch–Schönlein Purpura in Children

Abstract: Matrix metalloproteinase-9 (MMP-9) is an enzyme that implicates in the pathogenesis of renal diseases. HenochSchönlein purpura nephritis (HSPN) is the most serious long-term complication of Henoch-Schönlein purpura, and it is one of the most common renal diseases in children. There was no any meta-analysis to explore the association of MMP-9 level with the risk of HSPN, and this meta-analysis was performed to evaluate the association between MMP-9 level and HSPN risk in children. A predefined literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The pooled statistics were counted using the fixed effects model, but a random effects model was used when the p value of the heterogeneity test was less than 0.1. 10,11 Results were expressed with odds ratios (OR) for dichotomous data, and 95% confidence intervals (CI) were also calculated. p50.05 was required for the pooled OR to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled statistics were counted using the fixed effects model, but a random effects model was used when the p value of the heterogeneity test was less than 0.1. 10,11 Results were expressed with odds ratios (OR) for dichotomous data, and 95% confidence intervals (CI) were also calculated. p50.05 was required for the pooled OR to be statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…There are also reports of increased levels of matrix metalloproteinases (MMPs) in the fluid from bullous lesions demonstrated by immunochemistry staining [19]. This is an interesting finding because a recent meta-analysis of pediatric patients with HSP by Zhou et al found a strong association of nephritis with serum and even urinary levels of matrix metalloproteinase-9 [OR=77.21, 95% CI: 54.56–99.86 and p<0.00001] [20]. Our patient had no past history of bullous lesions but he probably did have association with pressure areas because he wore elastic stockings.…”
Section: Discussionmentioning
confidence: 95%
“…In a meta-analysis evaluating eight studies, the serum MMP-9 level was reported to be a risk factor for the development of HSPN (26). All eight studies were conducted in a Chinese population, with seven published in Chinese and only one published in English (7).…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis evaluating four studies, the urinary MMP-9 level was found to be increased in patients with HSPN and hence it could be used as an early indicator (26). In this study, the urinary MMP-9 level of the patients with HSPN was higher than that of the patients without renal involvement and the control group.…”
Section: Discussionmentioning
confidence: 99%